Capacidade antioxidante da saliva em indivíduos com Síndrome de Down em presença de doença periodontal - Rodrigues, Thamiris Orrico [UNESP] (2015)
Periodontal problems affect about 100% of individuals with Down syndrome (DS) at 30 years of age. The hypothesis that the reduction of negative regulation of oxidative metabolism in patients with DS may exacerbate the inflammatory response causing increased severity of periodontal disease (PD) stimulated the development of this study. It aimed of quantifying the antioxidant activity, the level of a biomarker of oxidative stress and analyzing clinical parameters relating to PD. For this, 28 individuals with PD were selected, including 18 with DS and 10 non-syndromic (control), which underwent a periodontal examination and had saliva collected before and 45 days after the non-surgical periodontal therapy. Total saliva was collected in the morning after fasting for 2 hours, using a portable vacuum sucking, and stored in a freezer at -80 °C until the time of analysis. In the first study, we evaluated the activity of antioxidants: superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT). For SOD and GPx colorimetric kits were used and CAT was determined by decomposition of hydrogen peroxide. The results were obtained by spectrophotometry at wavelengths of 550 nm, 340 nm and 240 nm, respectively. In the second study, we assessed the damage caused by oxidative stress through its main product, malondialdehyde (MDA) and by total antioxidant capacity (TAOC) in saliva. The level of MDA was based on the reaction of trichloroacetic acid (TCA), butilhidroxitoluol (BHT) and thiobarbituric acid (TBAR). Analysis of TAOC was made by colorimetry. The results were obtained by 20 spectrophotometry in the lengths of 535 nm and 660 nm, for TAOC and MDA respectively. Data, depending on the normality or not, were evaluated by ANOVA / Mann-Whitney, complemented by Tukey / Wilcoxon tests (α = 0.05). There was an improvement... ((Complete abstract electronic access below)